The Effects of Transactional Barriers on the Effectiveness of a Firm’s Competitive Strategy - Obu, Osiebuni; Ukpere, Wilfred (Journal of Economic Development, Environment and People, 2023)
Extant literature has shown that firms’ decisions can exert a bearing on the effectiveness of their competitive strategy. This paper seeks to extend this body of literature by demonstrating how and under what circumstances a firm’s decision about transactional barriers, which it can impose on its customers, can impact the degree to which it can effectively deploy its competitive strategy in realizing its maximum possible profits. The study’s main findings demonstrate that at equilibrium, the size of the set transactional barrier is on average inversely related to the effectiveness of the firm’s competitive strategy, holding constant the consumers' income and other factors. Furthermore, the effectiveness of the firm’s competitive strategy in attaining the firm’s optimal profits is jointly and individually enervated by the price elasticity of the firm’s product demand and the size of the transactional barrier that it imposes on its customers. Additionally, the effectiveness of the firm’s competitive strategy tends to be maximized as the size of the transactional barrier tends to be zero. Therefore, the findings in this paper suggest that under the assumptions of the model in this paper, the optimal size of a transactional barrier to be imposed by a firm, in the service industry, should be zero.